Jajanan Sehat Dan Bahaya Junk Food Pada Orang Tua Dan Sekolah - Maulana, Rizkha; Maulana, Rizky; Eldo, Hendry; Sari, Mena; Karimi; Zainuddin, Zulfa (Universitas Mataram, 2023)
The growth and development of school age children must be optimal, such as providing nutrition in good and correct quantity and quality, if not correct. An effective way to do this is through health promotion regarding healthy snacks and the dangers of junk food. This community service activity is intended for parents and schools to reduce the contribution of school-aged children to unsafe and unhealthy street snacks. Health promotion activities at SD N.18. Bireuen was held from January to June using digital methods delivered via Whatsapp group, carried out pre and posttests then presented using leaflets, videos and followed by discussions. There has been an increase in knowledge and attitudes of parents and schools regarding healthy food and the dangers of junk food.